2021
DOI: 10.1515/libri-2020-0166
|View full text |Cite
|
Sign up to set email alerts
|

Technological Readiness and Computer Self-efficacy as Predictors of E-learning Adoption by LIS Students in Nigeria

Abstract: The study focused on technological readiness and computer self-efficacy as predictors of E-learning adoption by Library and Information Science (LIS) students in Nigeria. While literatures have suggested that E-learning adoption is context based, there is a need to examine the predictors of E-learning adoption within the Nigerian context, given the increasing need for E-learning adoption as a result of the COVID-19 Pandemic. As a result, the study used the descriptive correlational research design to study a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…An M-learning platform is a distance learning platform with many features that support the learning and teaching processes for all education levels in universities. It also contributes to ensuring that lesson plans are carried out and the educational goals of the curriculum are met [50][51][52][53]. An M-learning system features a package of educational tools to support the teaching and learning processes.…”
Section: Overview Of Mobile Learning As a Distance Learning Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…An M-learning platform is a distance learning platform with many features that support the learning and teaching processes for all education levels in universities. It also contributes to ensuring that lesson plans are carried out and the educational goals of the curriculum are met [50][51][52][53]. An M-learning system features a package of educational tools to support the teaching and learning processes.…”
Section: Overview Of Mobile Learning As a Distance Learning Toolmentioning
confidence: 99%
“…Insufficient ITI resources can impede the acceptance and usage of any new technology [49]. Previous studies [50][51][52][53] have indicated that ITI is one necessary component of M-learning acceptance as shown in Figure 2. As a result, ITI in Saudi universities requires extensive analysis.…”
Section: Hypotheses Of the Proposed Modelmentioning
confidence: 99%
“…The consistent advancement in technologies has given birth to what is today known as open access technologies. Okuonghae et al (2021) defined open access technologies as technologies that are widely accessible by the populace and such technologies are committed to improving the products and services of organizations, businesses and institutions. Renkema (2016) noted that most open access technologies operate a creative commons license which allows for reuse and upgrading.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers criticized TAM and UTAUT for ignoring the technological factors such as security and privacy (Shachak et al, 2019). The technological readiness which includes the readiness of technical staff who are able to deploy the technology as well as the readiness of the governmental organization' infrastructure in term of network, software, hardware, and other technological tools has been examined by limited number of studies (Kim & Kim, 2022;Okuonghae et al, 2022). Therefore, this study investigates the usage of CC by governmental organizations in developing countries such as Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%